Collective political action in the Turkish press (1950-1980) - Akaş, Cem, 1968- (Thesis (Ph.D.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2004., 2004)
This dissertation examines the types of collective political action undertaken in Turkey between 1950 and 1980. Instead of examining the period in a purely chronological order, this study groups types of collective action together, and describes and analyzes them in chronological development. Seven such groups are identified: association formation, symbolic action, action in writing, demonstrations and protests, collective action involving the press, boycotts and sit-ins, and contentious action involving violence. The research for this study is based primarily on a close reading of the newspapers of the period, coupled with the application of the relevant theoretical literature in analyzing the history of collective action in Turkey. The study has found that such action has been wide-spread in Turkey since the beginning of the democratic era, even during periods of exceptional repressive measures taken by governments to stifle all forms of criticism and opposition. The types of action range from the universal (found in most contentious political action all over the globe) to actions unique to Turkish society; some types of popular action have also been adapted to local conditions and requirements. The variety of these types, however, steadily diminished in the 1970s and was eventually blotted out by a single type: violent action. The role of the youth and the military as the designated guardians of the regime has very much determined both the ideology of actors and the types of action they undertook.
Keywords: Political participation -- Turkey.